PENERAPAN SEO (SEARCH ENGINE OPTIMIZATION) MENGGUNAKAN TEKNIK TOGETHER IN A SINGLE CONNECTION (TSC) DALAM MENINGKATKAN KUNJUNGAN PADA SEBUAH BLOG - Setyaningsih, Devia Tito; Wintolo, Hero; Nugraheny, Dwi (Compiler, 2012)
One of the internet service used by the people of Indonesia is a blog that can be accessed via http://blogspot.com or http://wordpress.com and others. Everyone can use this medium for the purpose of publication of information in the form of text, images, sounds, or video without having to master web programming languages. One of the obstacles a person who has a blog is a way of increasing number of visitors to his blog. In order for many visitors the blog owner needs to understand about SEO (Search Engine Optimization).To allow users to blog in increasing the number of visitors and ranking his blog, they invented a system that utilizes parallel processing techniques and create a new method, named TSC (Together in a Single Connection) to increase the number of visitors, number of pages viewed and ranking.Increase blog traffic system based on parallel processing can improve the effectiveness in increasing traffic to a blog. With this system the blog owner is expected to be easier to rise to visit his blog.